Implementing the GROW Coaching Model in Developing Competencies of Educators: A Meta-Analysis - Yosua Damas Sadewo; Pebria Dheni Purnasari; Totok Victor Didik Saputro; Silvester Silvester; Nurselam Hassen Yimer (International Journal of Social Learning (IJSL), 2026)
The GROW coaching model has gained attention in educational contexts, yet empirical evidence regarding its effectiveness remains varied. Differences in research designs, performance indicators, and implementation have produced fragmented findings, making it difficult to obtain a consistent understanding of the model’s impact. This study aims to analyze this gap through meta-analysis. A total of 22 empirical studies were analyzed using a random-effects model, supplemented with heterogeneity tests, forest plot analysis, effect size calculations, and publication bias identification. The meta-analysis yielded a pooled effect size of 0.43, indicating a moderate level of effectiveness with no evidence of publication bias. These findings demonstrate that the GROW model consistently contributes to the development of multiple domains of educator competence, including managerial skills, supervisory abilities, and teaching and learning practices. Overall, the results affirm that the GROW model reliably supports educator competency development, although its effectiveness remains shaped by contextual factors.